2020
DOI: 10.1101/2020.10.06.327635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GNS561 exhibits potentin vitroantiviral activity against SARS-CoV-2 through autophagy inhibition

Abstract: Since December 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2/2019-nCoV) has spread quickly worldwide, with more than 29 million cases and 920,000 deaths. Interestingly, coronaviruses were found to subvert and hijack the autophagic process to allow their viral replication. One of the spotlights had been focused on the autophagy inhibitors as a target mechanism effective in the inhibition of SARS-CoV-2 infection. Consequently, chloroquine (CQ) and hydroxychloroquine (HCQ), a derivative of CQ,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A recent study has also shown that SARS-CoV-2 infection inhibits the Akt-mTOR pathway, which is thought to be involved in the induction of autophagy inVero E6 cells [60]; however, ORF3 of SARS-CoV-2 was proven to block the fusion of autophagosomes with lysosomes and to induce incomplete autophagy [55,61]. Indeed, controlling the autophagic process induced by these viruses plays an important role in antiviral activity [62][63][64][65]. However, in the current study, SARS-CoV-2, panH1N1, and H7N9 infection upregulated the expression of autophagy-related genes, such as ATG7, MAPK3, MLST8, BMF, and UCHL1 in A549 cells (https://doi.org/10.5281/zenodo.5489734, accessed on 15 November 2021), which indicated that autophagy is essential for virus pathogenicity, and inhibiting autophagic processes may become a universal antiviral strategy for influenza viruses and SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also shown that SARS-CoV-2 infection inhibits the Akt-mTOR pathway, which is thought to be involved in the induction of autophagy inVero E6 cells [60]; however, ORF3 of SARS-CoV-2 was proven to block the fusion of autophagosomes with lysosomes and to induce incomplete autophagy [55,61]. Indeed, controlling the autophagic process induced by these viruses plays an important role in antiviral activity [62][63][64][65]. However, in the current study, SARS-CoV-2, panH1N1, and H7N9 infection upregulated the expression of autophagy-related genes, such as ATG7, MAPK3, MLST8, BMF, and UCHL1 in A549 cells (https://doi.org/10.5281/zenodo.5489734, accessed on 15 November 2021), which indicated that autophagy is essential for virus pathogenicity, and inhibiting autophagic processes may become a universal antiviral strategy for influenza viruses and SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…10 ( 94 ) Mefloquine In vitro 3.85 ± 0.24 8.78 Preclinical 211 In vitro 8.06 18.53 Preclinical 245 In vivo 3.2 >10 Preclinical 94 Fig. 10 ( 95 ) Dithioerythrol thiosulfonate 16 In vitro 50 >500 Preclinical 214 GNS561 In vitro 0.006 for USA-WA1/2020; 0.03 for IHU MI6 2.0 for USA-WA1/2020; 6.7 for IHU MI6 Preclinical 215 Fig. 10 ( 96 ) VPS34-IN1 In vitro 0.55 >50 Preclinical 218 Fig.…”
Section: Sars-cov-2 Life Cycle and Potential Targets For The Development Of Small-molecule Inhibitors Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…Halfon et al 215 reported that GNS561 showed most potent antiviral effect against two SARS-CoV-2 strains (IC 50 = 0.006 μmol/L for USA-WA1/2020 and IC 50 = 0.03 μmol/L for IHU MI6; MOI = 0.1) compared to chloroquine and remdesivir ( Table 3 ). GNS561, located in LAMP2-positive lysosomes, together with SARS-CoV-2, blocked autophagy by increasing the size of LC3-II spots and increasing the volume of autophagic vacuoles in the cytoplasm with the presence of multilamellar bodies characteristic of a complexed autophagy 215 .…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Host Proteinsmentioning
confidence: 99%
“…In fact, recent studies have demonstrated that drugs with mechanistic similarity to CQ/HQC revealed inhibitory activity against SARS-CoV-2. For instance, GNS561, a small basic lipophilic molecule that induces lysosomal dysregulation and inhibition of the late-stage of autophagy, demonstrated potent in vitro antiviral activity against the novel SARS-CoV-2 alone and in combination with remdesvir [ 118 ]. Currently, GNS561 is being tested in cancer patients with moderate COVID-19 (National Institute of Health (NIH)-Clinical Trials Database; Identifier: NCT04333914) [ 119 ].…”
Section: Autophagy-related Therapeutic Targets For Covid-19 Managementmentioning
confidence: 99%